MINAT BACA BUKU SOSIOLOGI MENINGKATKAN HASIL BELAJAR XI IPS SMAN 3 PONTIANAK - Andika Putra, Abang (Jurnal Pendidikan Sosiologi dan Humaniora, 2018)
This study aims to know the students read the book sociology to improve learning outcomes in class XI SMA Negeri 3 Pontianak. This research method using descriptive qualitative. This research data source class XI IPS and data is data amid the semester test scores of students into information for researchers. Through observation, interviews and documentation to guide data collection tools of observation, interview guides. Results from this study showed that supporting students' interest in sociology books: factors originating from within the students such as concern, excitement, and a willingness to provide time for mebaca. There are also factors that come from outside the student namely the role of the teacher is always memperngruhi motivate the willingness and tendency to always read. Other than that, facilities support activities to read that the library and the internet have been provided making it easier for students to find the sources of reading material. Students read the book sociology to improve learning outcomes in class XI IPS SMAN 3 Pontianak interests and learning outcomes are pretty good on the subjects of sosilogi because they said there attitudes interest in the ability to conduct reading concerning the cognitive Understand the content of reading, as well as affective trying to read and study harder and psychomotor ask if there is not yet understood.